Peran Sumpah Pemuda dalam Mempersatukan Organisasi Pergerakan Nasional - Ajeng Priska Sari; Alya Nataly; Esa Indriani Br Bangun; Rosmaida Sinaga; Siti Julaiha (Journal on Education, 2024)
The National Movement was a time of increasing awareness of the Indonesian people to fight for liberation from colonialism. As time went by, organizations emerged under the leadership of young people who fought against the colonialists and achieved independence. The emergence of youth organizations in the national movement was motivated by four factors, namely educational, socio-cultural, socio-economic and political factors. The emergence of youth organizations is divided into two types, namely national movement organizations and regional movement organizations. The foundation of the struggle for the youth organizing movement began with the founding of Budi Utomo in 1908, which motivated the younger generation to establish an independence struggle organization. Organizations founded during the national movement after the founding of Budi Utomo included the Indonesian Association (1908), John Java (1915), John Sumatranen Bond (1917), and John Minahasa (1918), John Celebes (1919), and John Ambon ( 1917). John Batax Bond (1926), Sekhar Rukun (1919), John Timoresh Verbond (1921), Betawi Youth (1926), Indonesian Student Association (1926). Through the existence of socio-cultural based youth organizations and the sustainability of organizations with regional characteristics, we aim to establish and strengthen ties between members of organizations from each region. Therefore, this article aims to provide a theoretical explanation regarding the role of youth organizations in national movements. The data collection method used is library research through various sources including books, articles and other sources related to the Japanese population in Indonesia.